Association between human herpesviruses and multiple sclerosis: A systematic review and meta-analysis. (April 2023) - Khalesi, Zohreh; Tamrchi, Vahid; Razizadeh, Mohammad Hossein; Letafati, Arash; Moradi, Pouya; Habibi, Arezoo; Habibi, Negar; Heidari, Jafar; Noori, Maryam; Nahid Samiei, Mahboubeh; Azarash, Ziba; Hoseini, Mahdiyeh; et al.
Abstract: Aim: The aim of this study was to investigate the prevalence and potential association between infection with different herpes viruses and multiple sclerosis (MS). Methods: A systematic literature search was performed by finding relevant cross-sectional and case-control studies from a large online database. Heterogeneity, Odds ratio (OR), and corresponding 95% Confidence interval (CI) were applied to all studies by meta-analysis and forest plots. The analysis was performed using Stata Software v.14. Results: One hundred and thirty-four articles (289 datasets) were included in the meta-analysis, 128 (245 datasets) of which were case/control and the rest were cross-sectional. The pooled prevalence of all human herpes viruses among MS patients was 50% (95% CI: 45–55%; I2 = 96.91%). In subgroup analysis, the pooled prevalence of Herpes simplex virus (HSV), Varicella-zoster virus (VZV), Epstein–Barr virus (EBV), Cytomegalovirus (CMV), Human herpes virus 6 (HHV-6), Human herpes virus 7 (HHV-7), and Human herpes virus 8 (HHV-8) was 32%, 52%, 74%, 41%, 39% 28%, and 28%, respectively. An association was found between infection with human herpes viruses and MS [summary OR 2.07 (95% CI (1.80–2.37); I2 = 80%)]. Conclusion: The results of the present study showed that EBV, VZV, and HHV-6 infection are associated with multiple sclerosis and can be considered as potential risk factors for MS. Although the exact molecular mechanism of the role of herpes viruses in the development of MS is still unknown, it seems that molecular mimicry, the release of autoreactive antibodies, and inflammation in the CNS following viral infection can be important factors in the induction of MS. Highlights: The pooled prevalence of human herpes viruses among multiple sclerosis patients was 50% (95% CI: 45–55%; I 2 = 98.71%). An association was found between infection with human herpes viruses and MS [summary OR 2.07 (95% CI (1.80–2.37); I2 = 80%)]. An association of EBV, HHV-6, and VZV infection with MS was [summary OR 3.33 (95% CI 2.54–4.35)], OR 2.81 (95% CI 2.29–3.47), and OR 1.83 (95% CI 1.07–3.13) respectively. These results suggest that EBV, HHV-6, and VZV infection are associated with MS, and may be a potential risk factor for the development of MS.